The Effect Of Leadership And Internal Supervision On The Performance Of Health Workers At dr. Soepraoen Hospitals - Fita Rusdian Ikawati; Anis Ansyori; Retno Dewi Prisusanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
The performance of health workers who are in dr. Soepraoen Hospital is supervised by the leadership and carried out byinternal supervision. The purpose of writing this journal is to determine the effectiveness of the leadership and internal supervision carried out by the hospital on the performance of health workers. This research used quantitative with a cross sectional study approach. The location in this study is the Kindergarten Hospital. II dr. Soepraoen Malang which is located atJl. S. Supriadi No.22, Sukun, Kec. Sukun, Malang City, East Java 65112. The study was conducted from October to November 2020. Research The population in this study were all health workers who served in Kindergarten Hospitals. II dr. Soepraoen Malang at the time of the research, the number of health workers was 59 people. Samples were taken using total sampling. Data processing was performed using the SPSS for Windows application. Based on the research that has been done, it can be concluded that there is a positive and significant effect of leadership partially on health workers' performance, there is a positive and partially significant effect of partially internal supervision on health workers' performance, there is a simultaneous positive and significant effect of ethics leadership and internal supervision on health workers performance.